The Effect of Leadership on Digital Competence: The Moderating Role of Organizational Culture - Bagas Windu Panji Nata; Ribhan Ribhan; Keumala Keumala (Science and Education Journal (SICEDU), 2026)
The rapid advancement of digital technology has increased the demand for employees with strongdigital competence, particularly in the banking industry. Leadership is often regarded as a keydriver of digital capability development; however, empirical evidence regarding its effectivenessremains inconsistent, especially when organizational culture is considered. This study examinesthe effect of leadership on employees' digital competence and investigates the mediating role oforganizational culture. A quantitative research design with a causal approach was employed usingsurvey data collected from 203 banking employees in Jakarta and Lampung, Indonesia. Data wereanalyzed using Structural Equation Modeling (SEM). The findings reveal that leadership does nothave a significant direct effect on employees' digital competence. Nevertheless, leadership exerts asignificant indirect effect through organizational culture, indicating that an adaptive organizationalculture strengthens the influence of leadership on digital capability development. These resultssuggest that organizational culture functions as a crucial mechanism linking leadership withemployees' digital competence. Consequently, banking organizations should not rely solely onleadership development but should also cultivate a collaborative, innovative, and learning-orientedorganizational culture to accelerate digital transformation and improve workforce readiness. Thisstudy contributes to the digital leadership literature by demonstrating the strategic role oforganizational culture in enhancing digital competence within the Indonesian banking sector.